2023
DOI: 10.1039/d3ta00323j
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning chemical passivation over photovoltaic perovskites by varying the symmetry of bidentate acceptor in D–A molecules

Abstract: To pursue the efficient photovoltaic performance of perovskite solar cells (PSCs), a series of passivators have been employed to cure the defects of perovskite. A feasible strategy for designing efficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…At present, there are several strategies employed in the hole transport layer, such as formulating new doping strategies , or the utilization of alternative dopants to improve efficiency while ensuring stability. Furthermore, the development of new HTMs or dopant-free alternatives has been pursued to achieve long-term operational stability of PSCs. In addition, improving interface defects, regulation of perovskite crystallization, and prevention of perovskite degradation through interface engineering in PSCs can improve photovoltaic conversion efficiency. It is worth noting that a simple and straightforward approach to increase efficiency was recently reported, which involves the blend of two different HTMs within the device architecture. The mixed-HTM strategy involves combining two distinct HTMs in a composite layer that interfaces with the perovskite absorber. Taking advantage of the complementary properties of each HTM, the blend-HTM approach has the potential to significantly influence the charge transport and recombination processes within the device, ultimately improving the overall device performance.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are several strategies employed in the hole transport layer, such as formulating new doping strategies , or the utilization of alternative dopants to improve efficiency while ensuring stability. Furthermore, the development of new HTMs or dopant-free alternatives has been pursued to achieve long-term operational stability of PSCs. In addition, improving interface defects, regulation of perovskite crystallization, and prevention of perovskite degradation through interface engineering in PSCs can improve photovoltaic conversion efficiency. It is worth noting that a simple and straightforward approach to increase efficiency was recently reported, which involves the blend of two different HTMs within the device architecture. The mixed-HTM strategy involves combining two distinct HTMs in a composite layer that interfaces with the perovskite absorber. Taking advantage of the complementary properties of each HTM, the blend-HTM approach has the potential to significantly influence the charge transport and recombination processes within the device, ultimately improving the overall device performance.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, polycrystalline perovskite films are typically prepared via solution processing methods, which inevitably introduce defects such as uncoordinated Pb 2+ and halide ion (I – ) vacancies at the grain boundaries and interfaces between the perovskite layer and the electron-transporting layer (ETL). , Numerous studies have engaged to improve the crystallinity and morphology of the perovskite films and passivate defects on the surface or at the interface via various strategies, including additive implementation, , antisolvent engineering, and interface adjustment. , Particularly, interfacial engineering with functional semiconductors has been proved to be an effective approach for enhancing the PSCs’ photovoltaic properties along with facilitating the transportation of the charges, reducing defect density, and suppressing the recombination of the carriers, thereby promoting the crystal growth of the perovskite film and improving the photovoltaic performance of the solar cells. Among them, nanomaterial nitrogen-doped graphene quantum dots (N-GQDs) can act as an effective interface modulation reagent for efficient PSCs, which is utilized to ameliorate the following perovskite film quality and facilitate charge-transfer kinetics as well. Bian et al embedded N-GQDs on the surface of γ-CsPbI 3 -based PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that TA-CA with more significant adsorption energy of COOH and higher electron density of CN, in comparison to the dual CN groups in TA-MN, achieved poorer passivation and more defect density in perovskites. 19 In addition, Liang et al used a newly proposed 4,5-dicyanoimidazole (DCI) additive to arrange the lattice of 2D halide perovskites. They revealed that the DCI additive promotes the epitaxial growth of low- n phases along the growth direction to release internal lattice strain, regulates the lattice orientation, and reduces defects.…”
Section: Introductionmentioning
confidence: 99%